2011
DOI: 10.1016/j.jcps.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The consumer psychology of brands

Abstract: This article presents a consumer-psychology model of brands that integrates empirical studies and individual constructs (such as brand categorization, brand affect, brand personality, brand symbolism and brand attachment, among others) into a comprehensive framework. The model distinguishes three levels of consumer engagement (object-centered, self-centered and social) and five processes (identifying, experiencing, integrating, signifying and connecting). Pertinent psychological constructs and empirical findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
291
0
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(311 citation statements)
references
References 140 publications
3
291
0
17
Order By: Relevance
“…In the case of live music events these may be the musicians themselves, the venue, the alcohol consumed, the promotional, sponsorship or social marketing messages within the event. Schmitt (2012) suggests using techniques developed in neuroscience as one way to understand the effects of brand experience. However, this is not easily achieved in a real time naturalistic setting without intruding upon and influencing the experience.…”
Section: Experience and Live Eventsmentioning
confidence: 99%
“…In the case of live music events these may be the musicians themselves, the venue, the alcohol consumed, the promotional, sponsorship or social marketing messages within the event. Schmitt (2012) suggests using techniques developed in neuroscience as one way to understand the effects of brand experience. However, this is not easily achieved in a real time naturalistic setting without intruding upon and influencing the experience.…”
Section: Experience and Live Eventsmentioning
confidence: 99%
“…Hospitals tendency towards offering distinguished quality and according to customers' needs helps them be superior and valuable among customers. This also increases personality and serf confidence 34 . In subject hospitals in the present study competitive policies have been observed, which are a way of improving the level of performance and service acceptance 35 .…”
Section: Discussionmentioning
confidence: 97%
“…Beyond mere sensory stimulation, a brand can induce positive or negative moods and enable consumers to feel joyful and happy, or angry and sad (Schmitt, 2012) . These feelings or emotions may influence a consumer's level of attachment to the brand.…”
Section: Brand Identificationmentioning
confidence: 99%